Physical Activity in 15-17-Year-Old Adolescents as Compensation for Sedentary Behavior in School - Jakubec, Lukáš; Frömel, Karel; Chmelík, František; Groffik, Dorota (International journal of environmental research and public health, 2020)
The traditional concept of education and school settings significantly contribute to the sedentary behavior of adolescents at secondary schools. The aim of this study is to identify the volume and intensity of physical activity (PA) that adolescent boys and girls engage in during recesses, after school, and during the day to compensate for sedentary behavior in lessons. The study was conducted at 29 Czech and 9 Polish schools. The study involved 868 girls and 409 boys aged 15-17 years. An ActiTrainerTM accelerometer was used to monitor PA and heart rate. Participants were divided into four quartile groups. Most sedentary boys and girls had less PA and showed a worse ratio of physical inactivity (PI)/PA than non-sedentary participants during recesses. In the after-school period, there were no significant differences. On school days, most sedentary boys and girls showed lower PA, a worse ratio of PI/PA, fewer steps·hour-1, and lower energy expenditure than their non-sedentary counterparts. Vigorous PA of ≥8 METs was reached by 48% of most sedentary boys (75% non-sedentary) and 47% of most sedentary girls (54% non-sedentary). Most sedentary adolescents do not compensate for their sedentary behavior in lessons with higher PA intensity or volume during recesses, after-school, or in overall daily PA.
Keywords: Male; Polsko; sedavý životní styl; energetický metabolismus; Schools; Sedentary Behavior; intensity; Humans; Czech Republic; Česká republika; mužské pohlaví; Exercise; Female; mladiství; adolescent; ženské pohlaví; ActiTrainer; physical inactivity; školy; cvičení; Poland; Adolescent; lidé; Energy Metabolism